Réponses

  • Utilisateur Brainly
2013-04-21T19:37:15+02:00

E=14/15-1/21*1/(9/7-1/(1-1/2))

   =14/15-1/21*1/(9/7-2)

   =14/15-1/21*1/(-5/7)

   =14/15-1/21*(-7/5)

   =14/15+7/(21*5)

   =14/15+1/15

   =15/15

   =1

 

F=(3,5*10^-11*2*10^8)/(0,2*(10^-3)^3)

  =(3,5*2)/0,2*10^(-11+8-(-9))

  =35*10^6

 

G=(4*10^6)^-2

   =4^-2*10^-12

   =1/(4^2)*10^-12

   =1/16*10^-12

   =0,0625*10^-12

   =6,25*10^-14

 

H=(15*10^-4)/(42*10^-3)

   =15/42*10^(-4-(-3))

   =5/14*10^-1

   =5/140

   =1/28